Novel bio compactable silver nanowires and nanocubes: An effective treatment against carbapenem and vancomycin resistant strains isolated from cancer patients - Jiya Jose; Anju K. Nair; Nandakumar Kalarikkal; Oluwatobi Oluwafemi; Sabu Thomas (Journal of Saudi Chemical Society, 2019)
Blood stream infections in the cancer patients are a critical problem which leads to considerable rate of mortality and morbidity. In view of this herein, we account the response of Poly Vinyl Pyrrolidone (PVP) coated silver nanowires (Ag-NWs) and silver nano cubes (Ag-NCs) towards carbapenem (Escherichia coli) and vancomycin (Staphylococcus aureus) resistant strains as well as to human epithelial cells. The prepared PVP capped silver nanomaterials were in the range of 80 nm (Ag-NC) and 25 nm (Ag-NW) as observed from Transmission Electron Microscopy (TEM). Though the selected strains were resistant to carbapenem and vancomycin, PVP capped Ag-NWs and Ag-NCs could inhibit the growth of these strains. These nanomaterials could break the cell wall and damage the genetic material of these strains as observed by death rate assay and alkaline comet assay. Furthermore, we have shown that toxicity of Ag-NWs and Ag-NCs precisely follows the dose retort pattern. Even though the resistant strains were susceptible to a concentration of 10 µg ml−1 of silver nanomaterials the epithelial cells were not affected by the same concentration. It is also confirmed with live dead staining assay and observed that metabolic activities of epithelial cells were not affected by a concentration of 10 µg ml−1. Overall, this work suggests that these nanomaterials can be utilized to treat the multiple drug resistant strains from cancer patients. Keywords: Silver nanomaterials, Multiple drug resistance, Septicaemia, Genotoxicity, Biocompatibility, Cancer